The Neuronal Functions of EF-hand Ca(2+)-binding Proteins 2nd Edition - Beat Schwaller (Frontiers Research Topics, 2016)
Ca2+ signaling in neurons is characterized by highly restricted and dynamic gradients called Ca2+ waves, spikes, transients and puffs depending upon their corresponding spatial and temporal features. Based on this strict segmentation the Ca2+ ion provides a versatile basis for complex signaling in neuronal subcompartments with a spatial resolution of micro- and nanodomains. The multitude of Ca2+-regulated processes requires specialized downstream processing machinery, translating the Ca2+ signal into alterations of cellular processes. The broad range of different Ca2+-triggered phenomena in neurons, ranging from neurotransmission to gene expression, is reflected by the existence of a multitude of different Ca2+-binding proteins (CaBPs) from which numerous belong to the EF-hand super-family. EF-hand proteins can be subdivided into Ca2+ buffer and Ca2+ sensor proteins. Whereas the first group has a very high affinity for Ca2+, exhibits little conformational change in the Ca2+-bound state and is thought to mainly chelate Ca2+, the second group has a lower affinity for Ca2+ and shows considerable conformational changes upon Ca2+-binding, which usually triggers a target interaction. Neuronal calcium sensor (NCS) proteins and the related Caldendrin/CaBP/Calneuron (nCaBPs) proteins are members of this latter group. They resemble the structure of their common ancestor Calmodulin (CaM) with four EF-hand Ca2+-binding motifs, of which not all are functional. However, despite their structural homology with CaM, NCS as well as nCaBPs are quite diverse in amino acid sequence. It is therefore surprising that relatively few binding partners have been identified that are not CaM targets and this raises the question of the specificity and function of these interactions. In terms of function, binding of NCS and nCaBP has frequently different consequences than binding of CaM, which substantially increases the versatility of the Ca2+ tool kit. The general idea of this special issue is to provide an overview on the function of neuronal EF-hand calcium-binding proteins in health and disease. But we will not just provide a mere collection of articles to stress the function of each protein. The issue will mainly deal with emerging concepts on Ca2+-signaling/buffering mediated by EF-hand Ca2+-binding proteins. This includes questions like features that define the functional role of a EF-hand calcium sensor in neurons, the conditions that make physiological relevance of a given interaction of a CaBP with its target plausible, the emerging synaptic role of these proteins, and mounting evidence for their role in the regulation of protein trafficking. Structural aspects and biophysical studies will be covered. Another aspect will be the role of CaBPs in brain disease states. This aspect includes studies showing that CaBPs are targets of drugs in clinical use, studies showing that expression levels of calcium-binding proteins are frequently altered in brain disease states as well as reports on mutations in EF-hand calcium sensors linked to human disease.